Between Social Justice and Decolonisation: Exploring South African MOOC Designers’ Conceptualisations and Approaches to Addressing Injustices [journal article] - Adam, Taskeen (Journal of Interactive Media in Education, 2020)
As social justice and decolonisation discussions fill the physical and virtual corridors of universities in South Africa, educators, and in this case, MOOC designers, are inevitably influenced by them. They are prompted to reflect on such topics, whether in agreement or with scepticism. Provoked by one interviewee’s comment that ‘you could decolonise and still have an enormous amount of injustice’, this paper investigates how South African MOOC designers conceptualise (in)justice, and how they attempt to address these injustices in and through their MOOCs. As notions such as ‘social justice’ and ‘decolonisation’ have multiple meanings and connotations, a framework was created to unpack the ‘Dimensions of Human Injustice’ namely, material, cultural-epistemic, and political/geopolitical injustices. These dimensions of injustice were used to analyse semi-structured interviews with 27 South African MOOC designers. MOOC designers who stressed cultural-epistemic injustices, focused on relevance, inclusive processes and the geopolitics of knowledge production. Those who stressed material injustices, focused on socio-economic disparities, infrastructural inequalities and the need to tackle these systemic problems at a societal level. Through illustrating that MOOC designers attempt to address injustices based on their different conceptualisations of (in)justice, this study argues that a multi-pronged approach to tackling the various dimensions of injustice perpetuated in and through MOOCs can lead to more holistic justice-oriented MOOCs that better enable learners. Additionally, justice-oriented efforts by South African MOOC designers, highlighted in this paper, can be seen as a guide for the MOOC space in general to take greater strides in creating MOOCs in more justice-oriented ways.
Keywords: Author:OpenDevEd; MOOC designers; _C:Albania ALB; _C:South Africa ZAF; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; cultural-epistemic injustice; decolonisation; docs.opendeved.net; geopolitical injustice; material injustice; social justice